Role of Nitric Oxide in Thiol Mediated Ion Migration - Chitre, A.V. (Asian Journal of Chemistry, 2010)
Nitric oxide is recognized as a signalling molecule. It contributes to blood pressure regulation, neuronal communication, immune defence and vasodilator, etc. Recent studied have shown that blood serum levels of NO are on the higher side in enclampsia. Also it is observed that thiols in presence of superoxides form disulphide bonds between interacting systems affecting embryo implantation and electrolyte transport across placental membranes. The author has therefore attempted to study the effect of thiols on electrolyte (NaCl, KCl and CaCl2) migration and modifications, if any, of the same on addition of NaNO2 and sodium nitroprusside (Na-Np). It is observed that membrane ion equilibria, conductance and flow rates of solutions of electrolytes are influenced by thiols (bovine serum albumin BSA, glutathione, cysteine) and that addition of NaNO2 and Na-Np causes change in these. Turbidity of the thiol solutions is increased on addition of these nitro compounds. These observations indicate that thiols probably form some aggregates in presence of NO which affect their mechanism of ion transport resulting in pressure changes.